Form of Presentation of Pattudduq Sarawadang Dance in Majene Regency - Nanda Resma Yulianti; Agus Cahyono; Malarsih Malarsih (Catharsis, 2023)
Pattudduq Sarawadang dance is one of the traditional dances originating from the Mandar area, Majene Regency, which still exists today. The purpose of this study was to analyze and describe the form of presentation of the pattudduq sarawadang dance in Majene Regency. This type of research is case study-based qualitative. The method used is a qualitative method with an ethnochoreological approach. Research data were collected by interview, observation, and document study techniques. Checking the validity of the data using triangulation. The research data were analyzed qualitatively through the stages of data collection, data reduction, data presentation, and data verification or drawing conclusions. The results showed that the form of the Pattudduq Sarawadang dance includes movement, dancers, fashion/makeup, floor patterns, music, property and venue. There are six kinds of motion in dance. The Pattudduq Sarawadang dance is performed by women with an even number of at least four people. The properties used are fans and scarves. The accompaniment in dance uses drums, gongs, and keke instruments as well as singing. The place for the Pattudduq Sarawadang dance performance is in an open arena. The findings in this study are that there is a transformation or change in shape that occurs in the range of motion, dancers, costumes used, music and props in the Pattudduq Sarawadang dance.